Solder alloys, solder balls, solder pastes, and solder joints
Patent Information
- Application Number
- JP2023223551
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2043-12-28
Smart Images

Figure 0007633557000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a solder alloy, a solder ball, a solder paste, and a solder joint. [Background technology]
[0002] In recent years, there has been a demand for electronic devices to have higher integration, larger capacity, and faster speeds. For example, semiconductor packages such as BGA (Ball Grid Array) are being used to achieve higher integration and functionality at the semiconductor chip level.
[0003] For microelectrodes such as BGA, solder bumps are formed using solder balls. When using solder balls, for example, a sticky flux is applied to the microelectrode, and the solder ball is placed on the electrode to which the flux has been applied. The solder ball is then heated in a reflow furnace to melt, and the molten solder wets the microelectrode, forming a solder bump on the microelectrode. In this way, when using solder balls, wettability with the electrode is required.
[0004] Conventionally, Sn-Ag-Cu solder alloys have been widely used as solder alloys for forming solder bumps. This solder alloy is highly versatile and is used in various forms such as solder balls and solder paste. However, although this solder alloy is versatile, there are properties that must be further improved depending on the application such as solder balls and solder paste. Therefore, various studies have been conducted on the conventionally widely used Sn-Ag-Cu solder alloys to improve the properties according to the application.
[0005] Patent Document 1 discloses a solder alloy for automotive electronic components, which contains Ni as an essential element and may contain Co and Ge as optional elements in order to improve the vibration resistance of the Sn-Ag-Cu solder alloy. Patent Document 1 discloses that when a repeated bending test is performed to evaluate the vibration resistance, cracks occur in the intermetallic compound layer or in the solder alloy region depending on the alloy composition.
[0006] Therefore, Patent Document 1 discloses that in order to suppress the progression of fracture in the intermetallic compound layer, Ni or Co, which is an atomic species having a smaller atomic radius than Cu, is substituted for Cu in the SnCu compound, thereby alleviating the distortion of the intermetallic compound layer. It also discloses the addition of Fe, Ni, and Co to suppress the progression of fracture in the solder alloy region.
[0007] Patent Document 2 discloses a solder alloy in which Ni and Ge are essential elements in a Sn-Ag-Cu solder alloy and Co is an optional element, in order to improve shear strength and suppress non-fusion. Patent Document 2 also discloses that the balance between the Ag, Cu and Ni content and the Ge content is responsible for suppressing non-fusion. Patent Document 2 also discloses that shear strength is improved by refining the Cu and Sn compound and solid solution strengthening.
[0008] Patent Document 3 discloses a solder alloy in which the relational formula of each constituent element in a Sn-Ag-Cu-Ni-Co-Ge solder alloy is specified in order to suppress Ni erosion and the occurrence of voids. Patent Document 3 discloses that when each constituent element satisfies a predetermined relational formula, Ni diffusion is suppressed and voids occurring in the molten solder are easily discharged. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2007-237252 A [Patent Document 2] Patent No. 6928284 [Patent Document 3] Patent No. 6700568 [Patent Document 4] JP 2001-58286 A Summary of the Invention [Problem to be solved by the invention]
[0010] Patent Document 1 discloses Sn-Ag-Cu-Ni-Fe-Co solder alloy and Sn-Ag-Cu-Ni-Fe-Co-Ge-(P) solder alloy as solder alloys with the best results in repeated bending properties. In paragraphs 0036-0037 of Patent Document 1, it is stated that by adding a small amount of Fe, a large amount of FeSn2 intermetallic compound is generated as the nucleus of the primary crystal, the dendrite structure is refined, and excellent results are shown in the repeated bending test for evaluating vibration resistance. In addition, in paragraphs 0038-0039 of Patent Document 1, it is disclosed that when Ni, Co, and Fe are included, the thickness of the SnCu intermetallic compound layer is thin and grows uniformly. Furthermore, in paragraph 0056 of Patent Document 1, it is disclosed that Ge may be added to suppress discoloration of the solder surface.
[0011] The invention described in Patent Document 2 is an excellent invention that can suppress non-fusion and improve shear strength, and a relational expression of the content of the constituent elements is specified. Paragraph 0035 of Patent Document 2 describes that attention was paid to ΔT, which represents the temperature difference between the liquidus temperature and the solidus temperature, the viscosity of the molten solder, and Ge oxide. Paragraph 0038 of Patent Document 2 also discloses that the compound formed at the joint interface becomes fine by forming a (Cu,Ni)6Sn5 compound in which a part of Cu is replaced by Ni. Furthermore, the same paragraph describes a Sn-Ag-Cu-Ni-Ge solder alloy in which Ge dissolves in Ni, distorting the crystal structure of the compound and strengthening the (Cu,Ni)6Sn5 compound through solid solution.
[0012] The invention described in Patent Document 3 is an excellent invention that suppresses Ni erosion and void generation. Paragraph 0044 of Patent Document 3 discloses that it is possible to minimize the dissolution of the Ni layer by utilizing the sudden change in melting temperature caused by Ni. Paragraph 0045 of Patent Document 3 also discloses that the void discharge function by the convection of molten solder is maintained by forming a thin and brittle oxide film of germanium oxide instead of a strong tin oxide. Furthermore, paragraph 0054 of Patent Document 3 discloses that it is better to narrow ΔT in order to suppress the segregation of the alloy structure during solidification.
[0013] Thus, in Patent Documents 1 to 3, the improvement of vibration resistance, the suppression of discoloration, the suppression of non-fusion, the improvement of shear strength, and the suppression of Ni erosion and void generation are considered. However, in the inventions described in any of the patent documents, chip standing is not considered. Due to the rapid technological innovation in recent years, electronic components have been significantly reduced in size and weight. For this reason, if different amounts of solder alloy are supplied to two electrodes on which electronic components are mounted, chip standing may occur. Chip standing occurs when the chip is pulled by the surface tension of the solder alloy supplied to the two electrodes that melted first. This can be caused, for example, by different amounts of solder alloy supplied. In addition, there is a case where the amount of solder alloy supplied is different. In addition, there is a case where the amount of solder alloy supplied is different due to external factors, that is, when the solder alloy is mixed and mounted on the board, there is a case where the temperature rise of the solder alloy differs between peripheral components, etc., even if the amount of solder supplied is the same. Furthermore, in consideration of the behavior peculiar to the solder alloy, the solid phase changes to the liquid phase immediately after the solder alloy starts to melt. However, in the inventions described in Patent Documents 2 and 3, chip standing caused by these causes was not considered.
[0014] Here, in paragraph 0032 of Patent Document 4, it is disclosed that Ni, Cu, Co, Ge, etc. may be added to the Sn-Ag solder alloy to suppress chip standing. The same paragraph also discloses that the solder alloy to which these elements are added shows two endothermic peaks in differential thermal analysis. However, only the added elements are disclosed, and the solder alloys actually examined are only Sn-Ag, Sn-Ag-Cu, Sn-Ag-Ni, and Sn-Ag-P. Therefore, Co and Ge that may be contained in the solder alloys described in Patent Documents 1 to 3 have not been proven at all.
[0015] In addition, when the solder alloy is used in a substrate that is used in a harsh environment such as an in-vehicle device, excellent heat cycle resistance and drop impact resistance are required, but the above patent document does not consider heat cycle resistance.
[0016] Thus, even if the solder alloys described in Patent Documents 1 to 4 can solve the respective problems, it is desired that they better reflect the actual conditions when mounting electronic components. That is, the inventions described in these documents have not been examined to simultaneously satisfy the various properties disclosed in Patent Documents 1 to 4. Furthermore, the use environment has become harsher due to global warming in recent years, and a solder alloy that also satisfies excellent heat cycle resistance is desired.
[0017] Therefore, an object of the present invention is to provide a solder alloy, a solder paste, a solder ball, and a solder joint that have excellent heat cycle resistance and drop impact resistance, and that have excellent mountability by suppressing non-fusion, chipping, and discoloration. [Means for solving the problem]
[0018] The present inventors have investigated the characteristics of the Sn-Ag-Cu-Ni-Ge(-Co) solder alloys disclosed in Patent Documents 1 to 3. First, the inventors have found that the characteristics of the Sn-Ag-Cu-Ni-Ge solder alloy described in Patent Document 2 change depending on the content of each constituent element.
[0019] It was found that a solder alloy with an Ag content of 0.5% (Example 1 of Patent Document 2) had poor heat cycle resistance, but solder alloys with a high Ag content (Examples 2-4, 9-11, 14, and 16-22 of Patent Document 2) had improved heat cycle resistance. Even in these solder alloys with improved heat cycle resistance, depending on the alloy composition, they had poor drop impact resistance, and suffered from non-fusion, chipping, and discoloration.
[0020] Even in the case of a Sn-Ag-Cu-Ni-Ge-Co solder alloy (Example 29 of Patent Document 2) containing Co that refines the alloy structure, the drop impact resistance was poor, and chipping and discoloration occurred. Thus, it was found that the relationship described in Patent Document 2 is not sufficient to solve the above problems, and further investigation is necessary.
[0021] Patent Document 1 discloses a Sn-Ag-Cu-Ni-Ge-Co solder alloy in Example 89. However, it was found that the Ge content was as low as 0.005% and the Co content was as high as 0.040%, resulting in non-fusion and discoloration.
[0022] Patent Document 3 also discloses a Sn-Ag-Cu-Ni-Ge-Co solder alloy in Example 3. It has been found that discoloration occurs in this alloy composition because the Ge content is as low as 0.005%.
[0023] Thus, it became clear that even with a Sn-Ag-Cu-Ni-Ge(-Co) solder alloy, the required properties could not be obtained depending on the content of each constituent element. Here, in order to improve the heat cycle resistance and drop impact resistance, it is necessary to relieve the stress applied to the solder alloy, so it is desirable for the alloy structure to be fine. In order to make the alloy structure fine, it is considered that when the temperature drops slightly from the liquidus temperature, a large amount of the liquid phase becomes a solid phase, and each phase inhibits the growth of the other.
[0024] As mentioned above, chip standing occurs when the solder alloy introduced to the two electrodes melts at different times. It is presumed that in electronic components equipped with two electrodes, the upper end of the melted side of the chip component is pulled by the surface tension caused by the molten solder that melts first, resulting in chip standing.
[0025] More specifically, when the temperature of the molten solder rises from the solidus temperature to the liquidus temperature, even a slight rise in temperature from the solidus temperature causes the solid phase to become a large amount of liquid phase, and the effect of surface tension becomes large, which is believed to cause chipping. On the other hand, if the liquid phase does not form much even when the temperature rises from the solidus temperature, and the liquid phase finally begins to form in large amounts at a temperature close to the liquidus temperature, the effect of surface tension is relatively suppressed, and it is believed that chipping is unlikely to occur. Furthermore, it is believed that this behavior differs greatly depending on the alloy composition of the solder alloy, even if ΔT, which represents the temperature range between the solidus temperature and the liquidus temperature, is approximately the same.
[0026] On the other hand, in terms of the heat resistance of the chip, it was found that Sn-Ag-Cu-Ni-Ge-Co solder alloys tend to have a narrower ΔT temperature range and a lower liquidus temperature. For this reason, it is inferred that a narrower ΔT temperature range is better.
[0027] Furthermore, it is presumed that non-fusion occurs when a strong oxide film is formed on the surface of the solder alloy. On the other hand, discoloration can be suppressed when an appropriate oxide film is formed. Therefore, it is considered that appropriate oxidation is necessary to suppress non-fusion and discoloration.
[0028] From the above, in consideration of the behavior from the solidus temperature to the liquidus temperature, it is presumed that the heat cycle resistance, drop impact resistance, and chip standing have mutually opposing directions. Similarly, it is presumed that non-fusion and discoloration also have mutually opposing directions. With conventional solder alloys, it was difficult for these opposing alloy structures to simultaneously exert the effects required. In addition, in order to simultaneously satisfy excellent heat cycle resistance and drop impact resistance, it is considered necessary to refine the structure of the bonding interface and strengthen the Sn crystal grains in addition to making the alloy structure fine. Until now, in pursuit of each characteristic, alloy compositions that exert more effects than necessary have been sought, but it is considered that those that exert moderate effects evenly are more easily adapted to the actual situation of mounting.
[0029] Therefore, the inventors of the present invention have once again investigated in detail the content of each of the constituent elements so that all of the effects regarding the alloy structure and oxidation are simultaneously exhibited. As a result, it has been found that, for the first time, when the content of each of the constituent elements is within a specific range, the temperature range of ΔT is narrow, the alloy has excellent heat cycle resistance and drop impact resistance, and does not suffer from non-fusion, chipping, or discoloration, and the present invention has been completed based on this finding. The present invention, which has been made based on these findings, is as follows.
[0030] (1) A solder alloy having an alloy composition, in mass%, of 0.8-2.5% Ag, 0.10-1.00% Cu, 0.03-0.07% Ni, 0.006-0.014% Ge, 0.001-0.030% Co, and the balance being Sn.
[0031] (2) The solder alloy according to (1) above, further comprising, in terms of mass percent, at least one of Ga, As, Pd, Mn, In, Zn, Zr, and Mg in a total amount of 0.1% or less.
[0032] (3) The alloy composition is as follows: (1) ~(3) A solder alloy according to (1) or (2) above, which satisfies the formula. 400000≦Ag / (Cu×Ni×Ge×Co)≦1458334 (1) 2.50≦Ni / Co≦8.40 (2) 0.000168≦Ag×Cu×Ni×Co≦0.004900 (3) In the above formulas (1) to (3), Ag, Cu, Ni, Ge, and Co each represent the content in terms of mass % of the solder alloy.
[0033] (4) A solder ball comprising the solder alloy according to (1) or (2) above.
[0034] (5) A solder paste comprising the solder alloy according to (1) or (2) above.
[0035] (6) A solder joint comprising the solder alloy according to (1) or (2) above. [Brief description of the drawings]
[0036] [Figure 1] FIG. 1 shows cross-sectional SEM photographs of the solder alloy before and after a heat cycle test, where FIG. 1(a) is before the heat cycle test of Example 3, FIG. 1(b) is after the heat cycle test of Example 3, FIG. 1(c) is before the heat cycle test of Comparative Example 16, and FIG. 1(d) is after the heat cycle test of Comparative Example 16. [Diagram 2] FIG. 2 is an optical microscope photograph of the solder balls before and after exposure to high temperatures, where FIG. 2(a) is before exposure to high temperatures for Example 3, FIG. 2(b) is after exposure to high temperatures for Example 3, FIG. 2(c) is before exposure to high temperatures for Comparative Example 10, and FIG. 2(d) is after exposure to high temperatures for Comparative Example 10. [Diagram 3] FIG. 3 is a cross-sectional SEM photograph showing the presence or absence of non-fusion, where FIG. 3(a) is Example 3 and FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] The present invention will be described in more detail below. In this specification, "%" relating to the solder alloy composition is "mass %" unless otherwise specified.
[0038] 1. Solder Alloy (1) Ag: 0.8-2.5% Ag precipitates Ag3Sn in granular form, and improves the heat cycle resistance and drop impact resistance by strengthening the precipitation of the solder alloy. In addition, by lowering the melting point, the temperature range of ΔT can be narrowed and chipping can be suppressed. If the Ag content is less than 0.8%, the amount of compound precipitated is small and the heat cycle resistance is poor. If the Ag, Cu, and Ni contents are too small, the Ge content becomes relatively too high, so that the hard and brittle Ge oxide film is thickly covered, resulting in non-fusion. The lower limit of the Ag content is 0.8% or more, preferably 1.0% or more, and more preferably 1.2% or more.
[0039] On the other hand, if the Ag content exceeds 2.5%, the hardness of the solder alloy increases, and stress is concentrated at the joint interface, resulting in poor drop impact resistance. The upper limit of the Ag content is 2.5% or less, preferably 2.3% or less, more preferably 2.0% or less, even more preferably 1.6% or less, and particularly preferably 1.4% or less.
[0040] (2) Cu: 0.10-1.00% Cu suppresses the rise of the melting point. It can also suppress the precipitation of unfused or coarse Cu6Sn5. If the Cu content is less than 0.10%, Cu6Sn5 does not precipitate sufficiently, resulting in poor heat cycle resistance. The lower limit of the Cu content is 0.10% or more, preferably 0.20% or more, more preferably 0.30% or more, even more preferably 0.40% or more, and particularly preferably 0.50% or more.
[0041] On the other hand, if the Cu content exceeds 1.00%, coarse Cu6Sn5 precipitates at the bonding interface, resulting in poor drop impact resistance. Also, if the Cu content significantly exceeds 1.00%, the temperature range of ΔT expands, and there is a concern that non-fusion may occur. The upper limit of the Cu content is 1.00% or less, preferably 0.90% or less, more preferably 0.80% or less, even more preferably 0.70% or less, and particularly preferably 0.6% or less.
[0042] (3) Ni: 0.03-0.07% Ni suppresses the rise in melting point, suppresses non-fusion, promotes the refinement of Sn crystal grains, and improves heat cycle resistance and drop impact resistance. If the Ni content is less than 0.03%, the Sn crystal grains are not refined, and the drop impact resistance is poor. The lower limit of the Ni content is 0.03% or more, preferably 0.04% or more, and more preferably 0.05% or more.
[0043] On the other hand, if the Ni content exceeds 0.07%, coarse SnNi alloy precipitates on the surface of the solder alloy, causing non-fusion. In addition, the liquidus temperature rises, widening the temperature range of ΔT. Furthermore, if the Ni content is even higher, the drop impact resistance is also poor. The upper limit of the Ni content is 0.07% or less, preferably 0.06% or less.
[0044] (4) Ge: 0.006-0.014% Ge can suppress non-fusion and discoloration of the solder alloy. When Ge is not contained, tin oxide is formed on the surface of the molten solder. Tin oxide is strong and difficult to break. On the other hand, Ge added to the solder alloy reacts with oxygen in the atmosphere and forms a hard and brittle oxide film on the surface of the molten solder. This oxide film is brittle and is easily broken by the convection of the molten solder itself or the external force applied from the chip when the chip is placed. Therefore, the formation of the Sn oxide film is inhibited and the oxide film is not retained on the surface of the molten solder, and instead, the fusion of the solder balls and the solder powder in the paste is promoted, contrary to the Sn oxide film.
[0045] Ge also reacts with oxygen in the atmosphere to form a brittle oxide film, which can suppress discoloration of the solder alloy. Ge does not contribute to the suppression of supercooling, so the time until solidification is delayed and the Sn crystal grains become fine. Ge also has a longer-lasting oxidation prevention and suppression effect than P, which is used as an oxidation suppression element. Therefore, when Ge is used in solder balls in particular, it exerts the effect of refining the crystal grains of Sn and the effect of sustaining oxidation suppression.
[0046] If the Ge content is less than 0.006%, tin oxide is generated, causing discoloration. The lower limit of the Ge content is 0.006% or more, preferably 0.007% or more, and more preferably 0.008% or more. On the other hand, if the Ge content exceeds 0.014%, thick germanium oxide is generated on the surface of the solder alloy, and the hard and brittle Ge oxide film is thickly covered, causing non-fusion. In addition, non-fusion may occur similarly when the total amount of Ag, Cu, and Ni is relatively small. The upper limit of the Ge content is 0.014% or less, preferably 0.012% or less, more preferably 0.011% or less, even more preferably 0.010% or less, and particularly preferably 0.009% or less.
[0047] (5) Co:0.001~0.030% or less In the solder alloy according to the present invention, Co suppresses the rise in melting point, and by a synergistic effect with Ni, suppresses non-fusion, promotes the refinement of Sn crystal grains, and improves heat cycle resistance and drop impact resistance. In the solder alloy according to the present invention, the Co content is less than that of Ag and Cu, but the absence of Co results in poor drop impact resistance, non-fusion and chipping. For this reason, although Co is a trace additive element, it is treated as an essential element in the present invention.
[0048] If the content of Co is less than 0.001%, the refinement of Sn crystal grains is impaired, and the heat cycle resistance is poor. The lower limit of the Co content is 0.001% or more, preferably 0.004% or more, more preferably 0.006% or more, even more preferably 0.0070% or more, and particularly preferably 0.008% or more. On the other hand, if the content of Co exceeds 0.030%, coarse SnCo compounds are formed on the surface of the solder alloy, so that solid and liquid phases exist simultaneously in the molten solder, the liquidus temperature rises, and the wettability deteriorates, resulting in non-fusion. The upper limit of the Co content is 0.030% or less, preferably 0.020% or less, more preferably 0.015% or less, even more preferably 0.012% or less, and particularly preferably 0.010% or less.
[0049] (6) Remainder: Sn The balance of the solder alloy according to the present invention is Sn. In addition to the above elements, unavoidable impurities may be contained. Even if unavoidable impurities are contained, the above effects are not affected. Note that P acts as a solidification nucleus for Sn crystal grains to suppress supercooling, so it is better not to contain it because it takes longer to solidify and the Sn crystal grains become too large. In addition, in the present invention, there is a concern that Fe may form an intermetallic compound of SnFe. As a result, the difficulty of processing increases, so it is better not to contain it.
[0050] (7) At least one of the following elements: Ga, As, Pd, Mn, In, Zn, Zr, and Mg, total amount not exceeding 0.1% The solder alloy according to the present invention may contain at least one of Ga, As, Pd, Mn, In, Zn, Zr, and Mg as an optional element in a total amount of 0.1% or less to the extent that the effect of the present invention is not impaired. The total amount is preferably 0.08% or less. The lower limit of the content is not particularly limited, but may be 0.001% or more.
[0051] (8) (1) ~(3) formula 400000≦Ag / (Cu×Ni×Ge×Co)≦1458334 (1) 2.50≦Ni / Co≦8.40 (2) 0.000168≦Ag×Cu×Ni×Co≦0.004900 (3) In the above formulas (1) to (3), Ag, Cu, Ni, Ge, and Co each represent the content in terms of mass % of the solder alloy.
[0052] The solder alloy according to the present invention can fully exert all the effects by satisfying formulas (1) to (3). With respect to formula (1), Ag is an element that contributes to chip standing, and Cu, Ni, Ge, and Co are elements that contribute to effects other than chip standing. With respect to heat cycle resistance, drop impact resistance, and chip standing, the behavior from the liquidus temperature to the solidus temperature is contradictory, but it is better to exert a balanced effect overall without one effect being more prominent than necessary.
[0053] For this purpose, it is necessary to control the behavior of the liquid phase and the solid phase in the temperature range from the liquidus temperature to the solidus temperature. In order to meet the requirements in view of such circumstances, it is preferable that the solder alloy according to the present invention satisfies formula (1).
[0054] In addition, the solder alloy of the present invention satisfies formula (2), thereby improving the synergistic effect of Ni and Co to a sufficient level, and fully exerting the effect of refining Sn crystal grains. Furthermore, ΔT is narrow, and the occurrence of non-fusion is suppressed, and other effects can be achieved at the same time.
[0055] The solder alloy according to the present invention satisfies formula (3), and thus has an extremely good balance of the constituent elements that form compounds with Sn. Therefore, none of the AgSn compounds, CuSn compounds, NiSn compounds, and SnCo compounds precipitates in excessive amounts during solidification. As a result, the solder alloy that satisfies formula (3) has a high level of excellent heat cycle resistance.
[0056] The lower limit of formula (1) is preferably 400,000 or more, more preferably 428,571 or more, even more preferably 500,000 or more, even more preferably 535,714 or more, particularly preferably 600,000 or more, most preferably 625,000 or more, 714,286 or more, or even 750,000 or more. The upper limit of formula (1) is preferably 1,458,334 or less, more preferably 1,437,500 or less, even more preferably 1,250,000 or less, even more preferably 1,000,000 or less, particularly preferably 937,500 or less, and most preferably 875,000 or less.
[0057] The lower limit of formula (2) is preferably 2.50 or more, more preferably 3.75 or more, even more preferably 5.00 or more, and even more preferably 6.25 or more. The upper limit of formula (2) is preferably 8.40 or less, more preferably 8.33 or less, and even more preferably 7.50 or less.
[0058] The lower limit of formula (3) is preferably 0.000168 or more, more preferably 0.000180 or more, even more preferably 0.000192 or more, even more preferably 0.000200 or more, and particularly preferably 0.000240 or more. The upper limit of formula (3) is preferably 0.004900 or less, more preferably 0.000900 or less, even more preferably 0.000800 or less, even more preferably 0.000480 or less, particularly preferably 0.000460 or less, and most preferably 0.000400 or less, and may be 0.000336 or less, 0.000300 or less, 0.000280 or less, or 0.000252 or less.
[0059] These formulas are obtained by the mutual dependence of each constituent element. This is because an alloy is an integrated combination of all the constituent elements, and each constituent element affects each other. In this way, the solder alloy according to the present invention, which adjusts the content of each constituent element to an optimal value and further satisfies formulas (1) to (3), is set to a range that fully considers the mutual dependence of each constituent element. Therefore, when each constituent element is within the above-mentioned range and further satisfies formulas (1) to (3), various properties that were previously difficult to achieve can be achieved simultaneously and at a high level with one composition.
[0060] In the examples described below, the evaluation result of "◎" indicates that the result is particularly preferable in practical use compared to "◯". "◯" indicates a more preferable result than the conventional result, and is therefore within the scope of the present invention, and is treated as an example. "X" or "Δ" indicates an insufficient result in the present invention, and is therefore outside the scope of the present invention, and is treated as a comparative example.
[0061] 2. Solder balls The solder alloy according to the present invention can be used as a solder ball. The solder ball according to the present invention is used for forming electrodes of semiconductor packages such as BGA and bumps on substrates. The diameter of the solder ball according to the present invention is preferably within a range of 1 to 1000 μm. The solder ball can be manufactured by a general solder ball manufacturing method.
[0062] 3. Solder Paste The solder paste according to the present invention is a mixture of solder powder having the above-mentioned alloy composition and flux. The flux used in the present invention is not particularly limited as long as it allows soldering by a normal method. Therefore, a suitable mixture of commonly used rosin, organic acid, activator, thixotropic material, and solvent may be used. The blending ratio of the metal powder component and the flux component in the present invention is not particularly limited, but is preferably 70 to 90 mass % of the metal powder component and 10 to 30 mass % of the flux component.
[0063] 4. Solder joints The solder joint according to the present invention is suitable for use in joining at least two or more members to be joined. The members to be joined are not particularly limited as long as they are electrically connected using the solder alloy according to the present invention, and include, for example, elements, substrates, electronic components, printed circuit boards, insulating substrates, heat sinks, lead frames, semiconductors using electrode terminals, power modules, inverter products, and the like.
[0064] 5. Manufacturing method of solder alloy The solder alloy according to the present invention is preferably manufactured by adding Sn-Ni mother alloy, Sn-Co mother alloy, and Sn-Ge mother alloy to an alloy containing Sn, Ag, and Cu in a predetermined amount, so that the content of each constituent element is a predetermined amount. Since Ni and Co have high melting points, if added alone to Sn, they will remain unmelted, and the SnNi alloy and SnCo alloy will become coarse. Furthermore, since Ge has a high melting point, it will remain unmelted, and it cannot usually be added alone. For this reason, Ni, Co, and Ge are preferably added to the SnAgCu alloy in the form of a mother alloy with Sn.
[0065] 6. Other The solder alloy according to the present invention can be manufactured by using a low alpha radiation material as its raw material, and when such a low alpha radiation alloy is used to form solder bumps around a memory, it is possible to suppress soft errors. EXAMPLES
[0066] The present invention will be described with reference to the following examples, but the present invention is not limited to the following examples. In order to verify the effects of the present invention, (1) ΔT was measured, (2) a thermal cycle test (TCT), and (3) a drop impact test (DROP) were performed using the solder alloys shown in Table 1, and the presence or absence of (4) non-fusion, (5) standing chips, and (6) discoloration was confirmed.
[0067] (1) ΔT For the solder alloys shown in Tables 1 and 2, the respective temperatures were obtained from the DSC curves. The DSC curves were obtained by raising the temperature at 5°C / min in air using a Seiko Instruments DSC (model number: 6200). The liquidus temperatures were obtained from the obtained DSC curves. The solidus temperatures were also evaluated from the DSC curves. The value obtained by subtracting the solidus temperature from the liquidus temperature was taken as ΔT. When ΔT was less than 11°C, it was judged as "◎". When ΔT was 11°C or more and 40°C or less, it was judged as "〇". When ΔT was more than 40°C, it was judged as "△".
[0068] (2) Thermal cycle test (TCT) Each solder alloy shown in Tables 1 and 2 was atomized to make solder powder. A solder paste of each solder alloy was made by mixing with a soldering flux ("GLV" manufactured by Senju Metal Industry Co., Ltd.) consisting of rosin, solvent, activator, thixotropic agent, organic acid, etc. The alloy powder of the solder paste was 88% by mass, and the flux was 12% by mass. The solder paste was printed on a 0.8 mm thick printed circuit board (material: FR-4) with a 100 μm thick metal mask, and 15 BGA parts were mounted with a mounter and reflow soldered at a maximum temperature of 245°C and a holding time of 60 seconds to make a test board.
[0069] The prepared test board was placed in a heat cycle tester set to low temperature -40℃, high temperature +125℃, and a holding time of 10 minutes, and the number of cycles was determined at which the resistance value of at least one BGA component exceeded 15Ω from the initial resistance value of 3-5Ω. A cycle count of 700 or more was judged as "◎". A cycle count of 650-699 was judged as "◯". A cycle count of less than 650 was judged as "X".
[0070] (3) Drop impact test (DROP) Solder paste was prepared in the same manner as in (2). The solder paste was printed on a 0.8 mm thick printed circuit board (material: FR-4) using a 100 μm thick metal mask, and then five BGA components were mounted on each board using a mounter. Two test boards were then produced by reflow soldering at a maximum temperature of 240°C and a holding time of 60 seconds. The BGA components were then separated one by one.
[0071] Next, both ends of the test board were fixed to the base with bolts so that the BGA components faced the base. In this state, the board was subjected to an impact with an acceleration of 1,500 G while measuring electrical resistance in accordance with JEDEC standards to evaluate impact resistance. The progress of cracks was evaluated by the number of drops required until electrical resistance increased by 50% from the initial value. If the number of drops was 100 or more, it was judged as "◎". If the number of drops was 90 or more but less than 100, it was judged as "〇". If the number of drops was less than 90, it was judged as "X".
[0072] (4) Unfused The solder alloys shown in Tables 1 and 2 were inspected for the presence or absence of non-fusion. The inspection method was as follows: the solder alloys prepared according to the compositions of the Examples and Comparative Examples were cast and rolled, and then punched out to create small pieces (2 mm (length) x 2 mm (width) x 0.1 mm (thickness)). These small pieces were formed into plates of a given size, placed on a copper plate that had been treated with OSP (Organic Solderability Presevation) and coated with flux, and after reflow, the surface was washed and left in an environment of 125°C and 100% RH for 24 hours.
[0073] Furthermore, solder balls (diameter 300μm in this example) made of a solder alloy (Sn-3.0Ag-0.5Cu) consisting of 3.0% Ag, 0.5% Cu, and the remainder Sn were placed in an environment of 125℃ and 100%RH for 24 hours, similar to the small piece member. Next, flux was applied to a sample made of the solder alloy of the embodiment or comparative example, and a predetermined number of solder balls were placed on it. In this example, the number of solder balls was nine, and five of each were prepared. Then, after performing reflow in air at a maximum temperature of 240℃ and a holding time of 60 seconds, the number of unfused solder balls was counted. Unfused refers to a state in which the small piece and the solder ball are not bonded. When no unfused occurred, it was judged as "◎". When even one unfused occurred, it was judged as "X".
[0074] (5) Tip Stand Solder paste was prepared in the same manner as in (2). This solder paste was printed on the Cu lands of a 6-layer printed circuit board (FR-4, Cu-OSP) using a 150μm metal mask, and then 12 3216 chip resistors were mounted using a mounter. The solder was then melted and reflowed under heating conditions of a maximum temperature of 245°C and a holding time of 40 seconds, and soldered to prepare a test board. The number of standing chips after mounting was counted. If there were 0 standing chips, it was judged as "◎". If there was 1 standing chip, it was judged as "〇". If there were 2 or more standing chips, it was judged as "×".
[0075] (6) Discoloration The solder alloys shown in Tables 1 and 2 were placed in a crucible and heated at 245°C for 10 minutes to melt the solder alloy. The molten solder was then dripped from an orifice at the bottom of the crucible, and the resulting droplets were rapidly cooled to room temperature (18°C) and formed into solder balls with a diameter of 600 μm. The formed solder balls were heated for 300 seconds at 300°C in a thermostatic chamber in the atmosphere, and the change in lightness was measured. The lightness was measured using a Konica Minolta CM-3500d spectrophotometer, measuring the spectral transmittance with a D65 light source and a 10-degree visual field in accordance with JIS Z 8722 "Method of measuring color - Reflected and transmitted object color", and the color value (L * ,a * ,b* ) was calculated. Note that (L * ,a * ,b * ) is JIS Z 8729 "Color display method - L * a * b * Color system and L * u * v * This is specified in the "Color Space Specification System". * is the brightness, and a * is the redness, and b * is the yellowness. When the brightness was 70 or more, it was judged as "◎". When the brightness was less than 70, it was judged as "×". The results of the evaluation as described above are shown in Tables 1 and 2.
[0076] [Table 1]
[0077] [Table 2]
[0078] As shown in Table 1, in Examples 1 to 30, the contents of each constituent element were appropriate, and all evaluations showed results that were practically acceptable. In addition, it was found that Examples 2 to 5, 8, 9, 11, 12, 15 to 20, and 22 to 30, which satisfy the formulas (1) to (3), showed extremely excellent results in all evaluations.
[0079] On the other hand, as shown in Table 2, Comparative Example 1 had a low Ag content and therefore had poor TCT, and Comparative Example 2 had a high Ag content and therefore had poor DROP.
[0080] In Comparative Example 3, the TCT was poor due to the low Cu content, and in Comparative Example 4, the DROP was poor due to the high Cu content.
[0081] In Comparative Examples 5 and 6, the Ni content was low, so the DROP was poor. In Comparative Example 7, the Ni content was high, so non-fusion occurred and ΔT was widened. In Comparative Example 8, the Ni content was even higher, so non-fusion occurred, the TCT and DROP were poor, and ΔT was widened.
[0082] In Comparative Examples 9 to 11, discoloration occurred due to the low Ge content, whereas in Comparative Examples 12 and 13, non-fusion occurred due to the even higher Ge content.
[0083] In Comparative Example 14, the TCT was poor due to the low Co content. In Comparative Example 15, the Co content was high, so non-fusion occurred, and the ΔT was widened, non-fusion occurred, and discoloration occurred due to the high Co content.
[0084] In Comparative Example 16, since Co was not contained and Ag and Ni were also low, the TCT was poor and non-fusion occurred. In Comparative Example 17, since the Ge content was low, discoloration occurred. In Comparative Examples 18 to 24, since the Ge content was low and Ag content was high, the DROP was poor and discoloration occurred.
[0085] FIG. 1 shows cross-sectional SEM photographs of the solder alloy before and after the heat cycle test, with FIG. 1(a) being before the heat cycle test of Example 3, FIG. 1(b) being after the heat cycle test of Example 3, FIG. 1(c) being before the heat cycle test of Comparative Example 16, and FIG. 1(d) being after the heat cycle test of Comparative Example 16. As shown in FIG. 1(a) and FIG. 1(b), after the heat cycle test of Example 3, Sn and Ag3Sn around Sn became slightly coarse, but the coarsening was suppressed to a level that did not deteriorate the characteristics. On the other hand, as shown in FIG. 1(c) and FIG. 1(d), after the heat cycle test of Comparative Example 16, it was found that Sn, Ag3Sn, and (Cu,Ni)6Sn5 became significantly coarser.
[0086] Fig. 2 shows optical microscope photographs of solder balls before and after exposure to high temperature, with Fig. 2(a) being Example 3 before exposure to high temperature, Fig. 2(b) being Example 3 after exposure to high temperature, Fig. 2(c) being Comparative Example 10 before exposure to high temperature, and Fig. 2(d) being Comparative Example 10 after exposure to high temperature. As shown in Figs. 2(a) and 2(b), no oxidation of the solder balls was observed after exposure to high temperature in Example 3. On the other hand, as shown in Figs. 2(c) and 2(d), Comparative Example 10 was generally darkened after exposure to high temperature.
[0087] Figure 3 shows cross-sectional SEM photographs showing the presence or absence of non-fusion, with Figure 3(a) being Example 3 and Figure 3(b) being Comparative Example 8. As shown in Figure 3(a), it was found that fusion with the solder ball occurred in Example 3. On the other hand, as shown in Figure 3(b), it was found that non-fusion occurred in Comparative Example 8.
Claims
1. A solder alloy having an alloy composition, in mass%, of 0.8-2.5% Ag, 0.1-1.0% Cu, 0.03-0.07% Ni, 0.006-0.014% Ge, 0.001-0.030% Co, and the balance being Sn, and characterized in that ΔT, which is the value obtained by subtracting the solidus temperature from the liquidus temperature, is 40°C or less.
2. A solder alloy as described in claim 1, wherein the alloy composition further contains, by mass%, at least one of Ga, As, Pd, Mn, In, Zn, Zr, and Mg in a total amount of 0.1% or less.
3. The solder alloy according to claim 1 or 2, wherein the alloy composition satisfies the following formulas (1) to (3): 400000≦Ag / (Cu×Ni×Ge×Co)≦1458334 (1) 2.50≦Ni / Co≦8.40 (2) 0.000168≦Ag×Cu×Ni×Co≦0.004900 (3) In the above formulas (1) to (3), Ag, Cu, Ni, Ge, and Co are each the content in mass % of the solder alloy.
4. A solder ball comprising the solder alloy according to claim 1 or 2.
5. A solder paste comprising the solder alloy according to claim 1 or 2.
6. A solder joint comprising the solder alloy according to claim 1 or 2.
Citation Information
Patent Citations
Solder paste for joining chip part
JP2001058286A
Lead-free solder alloy for electronic member to be mounted on automobile, solder ball and electronic member
JP2007237252A
Solder alloy
JP2014057974A
Lead-free solder alloy
JP2017217693A
Solder alloy for lead-free and antimony-free, solder ball, ball grid array, and solder joint
JP2021028078A